2019
DOI: 10.1021/acsmedchemlett.8b00549
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Substituted Benzimidazolones as Potent HIV-1 Non-Nucleoside Reverse Transcriptase Inhibitors

Abstract: Since the discovery of HIV as the etiological agent of AIDS, the virus has infected millions of people each year. Fortunately, with the use of HAART, viremia can be suppressed to below detectable levels in the infected individuals, which significantly improves their quality of life and prevents the onset of AIDS. However, HAART is not curative and issues relating to adherence and drug resistance may lead to the re-emergence of viremia, the development of AIDS, and ultimately death. To address a pressing need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In the present study, the developed predictive RF model for HIV yields an average correlation of 0.81 with RMSE of 1.28 (− log M) in the nested CV assessment (see Table 5 ). Further evaluation of the RF model was performed using 10 novel compounds reported by Pribut et al [ 42 ]. According to their study, aryl substituted benzimidazolones were experimentally validated to exhibit inhibitory effects against the HIV-1 non-nucleoside reverse transcriptase, with the reported pIC50 values in the range of 4.87–7.58.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the developed predictive RF model for HIV yields an average correlation of 0.81 with RMSE of 1.28 (− log M) in the nested CV assessment (see Table 5 ). Further evaluation of the RF model was performed using 10 novel compounds reported by Pribut et al [ 42 ]. According to their study, aryl substituted benzimidazolones were experimentally validated to exhibit inhibitory effects against the HIV-1 non-nucleoside reverse transcriptase, with the reported pIC50 values in the range of 4.87–7.58.…”
Section: Resultsmentioning
confidence: 99%
“… a For the benchmark set, where no new suitable data were found in literature, the entries are marked as “–.” Sources of benchmark data are: Kinase [ 46 ], Ligase [ 47 ], BRD [ 45 ], CA [ 48 ], beta-secretase [ 49 ], HIV [ 42 ], and TB [ 50 ] …”
Section: Methodsmentioning
confidence: 99%
“…However, poor correlation of 0.56 was obtained, which was significantly lower than the originally reported correlation of 0.76 (Qureshi et al, 2018). Figure S5 We compared the binding modes predicted by PSOVina2 in LigTMap to the previously reported binding modes (Pribut et al, 2019). The three compounds were evaluated: 42, 50, and 54.…”
Section: Case Study Of the Hiv Drug Target Predictionmentioning
confidence: 98%
“…In the present study, the developed predictive RF model for HIV yields an average correlation of 0.81 with RMSE of 1.28 (-log M) in the nested CV assessment (see Table 4). Further evaluation of the RF model was performed using 10 novel compounds reported by Pribut et al (Pribut et al, 2019). According to their study, aryl substituted benzimidazolones were experimentally validated to exhibit inhibitory effects against the HIV-1 non-nucleoside reverse transcriptase, with the reported pIC50 values in the range of 4.87-7.58.…”
Section: Case Study Of the Hiv Drug Target Predictionmentioning
confidence: 99%
“…This issue was overcome through transposition of the aromatic functionality to position 7 of the benzimidaolone scaffold ( 94 ) whose activity against wild‐type HIV, was maintained against the Y181 C and the K103 N/Y181 C double mutant. In silico data suggested that this compound formed a new electrostatic interaction with Tyr188 and Trp229, thus negating the need for an interaction with Tyr181 …”
Section: Anti‐hiv Agentsmentioning
confidence: 99%